Spiritual intelligence of adolescents with diabetes based on demographic components - Mojdeh Rahmanian; Mohsen Hojat; Naima Seyed Fatemi; Abbas Mehran; Soroor Parvizy (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: Spiritual intelligence is better defined as a capacity to discover and develop true meaning, deep purpose, and vision in life. The purpose of the present study was to determine the predictive role of demographic variables affecting the overall spiritual intelligence in diabetic adolescents. METHODS: In 2016, a cross-sectional study was conducted involving 200 adolescents with type 1 diabetes referring to the Iranian Diabetes Association consenting to participate. The inclusion criteria were: age ranging from 15 to 21 years, more than a year since last diagnosed with diabetes, patients' full awareness of their disease, not having other physical-psychological illnesses, and not taking any psychiatric or narcotic drugs. Spiritual intelligence was measured using the Spiritual Intelligence Self Report Inventory questionnaire consisting of 24-questions. The alpha Cronbach's method was applied to validate the questionnaire in terms of content, form, and data with the reliability calculated as 0.903. Demographic data were analyzed using SPSS software version 18. RESULTS: On total, 56% of the participants were female, 17.10 ± 1.85, and the mean duration of diabetes was 5.98% ± 3.79%, 62.5% reported diabetes history among immediate relatives. Forty-two percent of the participants were the oldest child in the family first children of the family and 29.5% were studying at the university. The mean score of spiritual intelligence was 60.42 60.42 ing from 15 to 21 years regression test using the enter method (ANOVA: 0.703, F: 0.739) showed that none of the demographic components explored did not significantly alter the scores that assessed spiritual intelligence. CONCLUSION: The outcome of the current study portrayed that demographic features do not necessarily alter the overall spiritual intelligence scores, thereby not necessarily affecting an individual's overall spirituality.